Effect of Extracts of Boerhavia diffusa and Bryophyllum calycinum on Serum Uromodulin and Biochemical Profile of Rats Having Adenine Induced Chronic Kidney Disease - Singh, Madhu; Raval, Sunant K.; Parikh, Pinesh V.; Mandali, Ghanshyam C.; Bhanderi, Bharat B. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present instigation was carried out on 62 adult healthy male Wistar rats (12-15 weeks of age) to study the therapeutic efficacy of  Boerhavia diffusa (BD, roots) and Bryophyllum calycinum (BC, leaves) on adenine induced chronic kidney disease (CKD) through evaluation  of serum uromodulin and biochemical changes after therapy. The rats were randomly divided into 8 groups. Group I (n = 6) was given  only distilled water and served as healthy control. Groups II to VIII (n = 8 each) were given adenine chemical @ 200 mg/kg body weight  daily for 28 days by oral ravage needle to induce CKD. After 28th day, groups III and IV were given an aqueous and alcoholic extract of  BD, group-V, and VI with aqueous and alcoholic extract of BC @ 300 mg/kg body weight daily for 42 days. Group VII was given bihebral  aqueous extract of BC and BD (1:1.5), while group VIII received bihebral alcoholic extract of BC and BD (1:1.5) @ 300 mg/kg body weight  daily for 42 days. Results of serum uromodulin and biochemistry revealed that aqueous and alcoholic extracts of both the plants possess  good therapeutic/nephroprotective efficacy against CKD as reflected by a significant increase in the serum levels of uromodulin, ALT,  BUN, uric acid, creatinine, and phosphorus, with a decreased level of total protein in the CKD induced groups as compared to the normal  control group on 28th day followed by reversal towards normal values after 42 days of herbal therapy, i.e. on 70th day of an experiment,  in all groups, and particularly in groups VII and VIII co-treated with aqueous and alcoholic extracts of both plants. The effect of biherbal  alcoholic extract of the plants was much better in restoring the serum uromodulin and biochemical values of CKD-induced rats by 42  days of administration.
Keywords: Boerhavia diffusa; Bryophyllum calycinum; Herbal extracts; Nephroprotective effect; Serum biochemistry; Uromodulin; Wistar rats